(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Bajo refers to a name for ethnicity and language. Bajo people are found in Indonesia’s coastal areas; two are in South Sulawesi and West Nusa Tenggara. They are also well-known by a term called ‘sea gypsies.’ However, in the last two decades, they have started making settlements along Indonesia’s north coastal areas. These circumstances are exciting phenomena, and there is a need to assign such a study to their language status. The methods used are quantitative and descriptive. The quantitative method uses lexicostatistics—the descriptive method used for the culture study of the isolects. Data was gathered through interviews and documentaries. Results show that the two enclaves use the same language. The language status reaches 81%. It means that they are only different in dialectal cases.